2021
DOI: 10.1088/1757-899x/1073/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

HDPE plastic extruder design and control for 3D printing with plastic pellet feeding method

Abstract: 3-Dimensional (3D) Printing Technology (3D printer) has become a Standard Acceleration Tool for Industry 4.0. Until now, 3D Printing system material melting technology has been using Fused Deposition Modelling (FDM) method. FDM is the melting of plastic materials through melting temperature and the formation of 3D objects in layer by layer manner. Meanwhile, the feeding for melting material is in the form of rolling filament. Currently, in this research FDM uses plastic pellete feeding method. Its exstrusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In screw-based FDM systems, there is less material degradation due to homogenous material melting and homogeneous material flow [54]. Setiawan et al [61] successfully processed neat HDPE granules in a screw-based FDM technology and reported that the extrusion system was able to consistently extrude the molten plastic material at relatively low melting temperatures. The study reported no inhomogeneous material deposition and no under-extrusions.…”
Section: Extrusion Mechanism Modificationmentioning
confidence: 99%
“…In screw-based FDM systems, there is less material degradation due to homogenous material melting and homogeneous material flow [54]. Setiawan et al [61] successfully processed neat HDPE granules in a screw-based FDM technology and reported that the extrusion system was able to consistently extrude the molten plastic material at relatively low melting temperatures. The study reported no inhomogeneous material deposition and no under-extrusions.…”
Section: Extrusion Mechanism Modificationmentioning
confidence: 99%
“…In the development of re-retardant materials, there has been insu cient research on achieving adequate re-retardant performance and on deriving optimal performance through the use of various mixed ratios. [1] In this study, we aim to develop a pellet extruder capable of blending different materials and use it to print eco-friendly re-retardant materials with a large 3D printer, evaluating their characteristics. Unlike traditional 3D printing technology, which primarily uses single materials, this study aims to mix materials with different properties to impart new functionalities.…”
Section: Introductionmentioning
confidence: 99%